2022
DOI: 10.7150/ijbs.69495
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop of CENPU/E2F6/E2F1 facilitates proliferation and metastasis via ubiquitination of E2F6 in hepatocellular carcinoma

Abstract: Centromere protein U (CENPU), a centromere-binding protein required for cellular mitosis, has been reported to be closely associated with carcinogenesis in multiple malignancies; however, the role of CENPU in hepatocellular carcinoma (HCC) is still unclear. Herein, we investigated its biological role and molecular mechanism in the development of HCC. High CENPU expression in HCC tissue was observed and correlated positively with a poor prognosis in HCC patients. CENPU knockdown inhibited the proliferation, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The expression levels of E2Fs (E2F1-8) were all signi cantly upregulated in LUAD tissues [13], Wang et al investigated the expression, prognosis value, mutation, and potential relationship with immunological aspects of E2Fs in LUAD by bio-informatics analysis [13].E2F1 is expressed strongly in 59.8% of ESCC and that the over-expression was correlated with tumor progression, lymph node metastasis, and poor prognosis after surgery [15]. Over-expression of E2F1 was signi cantly associated to worsen OS in all NSCLC patients followed for 200 months, as well as in LUAD patients [24],which was duplicated in HCC patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of E2Fs (E2F1-8) were all signi cantly upregulated in LUAD tissues [13], Wang et al investigated the expression, prognosis value, mutation, and potential relationship with immunological aspects of E2Fs in LUAD by bio-informatics analysis [13].E2F1 is expressed strongly in 59.8% of ESCC and that the over-expression was correlated with tumor progression, lymph node metastasis, and poor prognosis after surgery [15]. Over-expression of E2F1 was signi cantly associated to worsen OS in all NSCLC patients followed for 200 months, as well as in LUAD patients [24],which was duplicated in HCC patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…OIP5 level has been shown to be enhanced at G1 phase [ 28 ], and it is localized to chromosomes at postmitotic stage [ 28 ]. Stable binding of OIP5 to centromeres is essential for recruitment of CENP-A [ 16 , 24 , 29 ]. These findings suggest that OIP5 is involved in regulation of cell cyclin proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Centromere protein U (CENPU) has been shown to accelerate the G1/S transition of hepatocellular carcinoma cell proliferation by interacting with E2F6 and affecting transcription of E2F1 [ 29 ]. The altered genes by CENPN knockdown are enriched in pathways related to cell cycle regulation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that the CENP genes are associated with multiple cancer metastases, CENPA is associated with breast and kidney cancer metastasis [68], and CENPF and CENPU are associated with prostate cancer metastasis [69,70]. CENPU is also involved in hepatocellular carcinoma and lung cancer metastasis [71,72]. The G2/M phase is regulated by CENPA, CENPF, and CENPW has been documented [73].…”
Section: Discussionmentioning
confidence: 99%